Comparative analysis of library services of five 2008 most outstanding libraries of Metro Manila - Pobre, Jacinto Victor C.; Dela Torre-Oliveros, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
The purpose of the public library is to provide access to books and other materials containing information that would cater to the needs of the population, helping them in the extension of their knowledge and experience. This study conducted a comparative analysis of the different services provided by the top five city libraries from Marikina, Pasig, Quezon City, Manila and Makati, based on four out of seven criteria used in the 2008 Search for Most Outstanding City Libraries of Metro Manila, namely services, programs, access, and physical facilities.
The study utilized survey research design, collecting the data over a period of two weeks using two research instruments. The checklist of library services accomplished by city librarians; and the user feedback questionnaire answered by respondents identified through quota sampling.
The main findings of the study showed that Marikina City Library and Quezon City Public Library are the libraries most compliant with the proposed Public Library Standards of the BFL and the IFLA/UNESCO Guidelines for Public Libraries. Quezon City Public Library was able to comply with provision for online public access catalog available through the internet. Makati City Library and Manila City Library failed to comply with the provision for the library to have its own building while Pasig City Library did not have provisions for ramps to access of the physically disabled individuals. Judges' ratings placed Marikina City Library on the top spot for the four categories used in the study however, based on the current survey of library services and facilities, the library tied with Pasig City Library on the top spot. Results from the user feedback showed that compliance with the standards does not always translate to user satisfaction. Manila City Library only ranked fourth in terms of providing services and facilities based on the standards; however, it was able to provide services that mattered to its constituents that translated to highest ratings in the user survey.
Recommendations of the study include a regular evaluation of users' needs and preferences by the libraries to be able to provide the most efficient services. It is also recommended that provisions for customer care be included in the proposed standards of the BFL.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Manila Metropolitan Area